Prevention and control of thalassemia in Guangdong Province, Southern China: insights from an 11-year retrospective study - Danqing Qin; Wei He; Jicheng Wang; Juan Zhu; Cuize Yao; Xiuqin Bao; Jie Liang; Yixia Wang; Kailing Liang; Mingyong Luo; Li Du; Jing Wu (Annals of Medicine)
Background Thalassemia, a prevalent monogenic inherited disorder, represents a significant public health concern in southern China. This comprehensive study retrospectively analysed prenatal diagnostic data for thalassemia over an 11-year period in Guangdong Province, a high-prevalence region in southern China.Methods Prenatal diagnosis (PND) of thalassemia was performed on 22,127 foetuses from at-risk pregnancies, following standardized protocols for invasive sampling, foetal sample collection and laboratory processing. Thalassemia mutations were identified using PCR-based molecular techniques.Results The analysis revealed that 16,812 cases (75.98%) were diagnosed with thalassemia, including 12,636 cases (57.11%) identified as α-thalassemia, 3961 cases (17.90%) as β-thalassemia and 215 cases (0.97%) as co-inheritance of α- and β-thalassemia. Among these, 5769 cases (26.08%) were diagnosed with intermedia or severe thalassemia genotypes, of which 2593 underwent pregnancy termination. Additionally, our study detected 275 cases of rare thalassemia variants. The retrospective analysis encompassed critical aspects including the timing of PND, genotype spectrum and rare variant identification, complemented by a synthesis of clinical practice insights.Conclusions This large-scale study provides substantial epidemiological data and clinical insights that significantly contribute to the enhancement of thalassemia prevention and control strategies in Guangdong Province.